Penerapan TIK dalam Pembelajaran PAI untuk Meningkatkan Motivasi Belajar Siswa di SMP Negeri 1 Kuwarasan Kebumen - Megasari, Arum; Eliyanto, Eliyanto Nur (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This study aims 1) To describe the application of Information and Communication Technology (ICT) in Islamic Religious Education (PAI) learning at SMP Negeri 1 Kuwarasan, Kebumen. 2) It also explores students' responses and perceptions of ICT-based PAI learning, and 3) dentifies supporting and inhibiting factors that arise in its implementation. This research is a qualitative research. The students studied were students of class VIII of SMP Negeri 1 Kuwarasan Kebumen, namely class VIII A and VIII H. The data collected were in the form of research observation data and interview results with the Principal, Islamic Religious Education Teachers and students of class VIII A and VIII H. The data analysis techniques used were data reduction, data presentation and drawing conclusions/verification. The results indicate that the application of ICT in PAI learning is quite optimal through the use of media such as PowerPoint, instructional videos, and animations appropriate to the material. Student responses to ICT-based learning tend to be positive, marked by increased participation, focus, and learning motivation. Supporting factors for ICT implementation include the availability of school facilities (projectors, laptops, internet), teacher competence, and student enthusiasm. Inhibiting factors include technical constraints such as unstable internet connections and sometimes blurry projector quality. This study confirms that the integration of ICT in PAI learning can create a more interactive, enjoyable, and relevant learning environment for the digital generation.